The Evaluation of Parental Acceptance Towards Children with Sex Chromosomal Disorders of Sex Development Using A Mixed-Method - Iit Fitrianingrum; Annastasia Ediati; Tri Indah Winarni; Sultana MH Faradz (Faculty of Medicine, Diponegoro University, 2021)
Background: Sex chromosomal Disorder of sex development (DSD) is an atypical abnormality of external genitalia which is mismatched with its sex chromosome traits. The condition of children with DSD affects the dynamics in the family. Parents’ reactions after discovering this health problem vary greatly, such as being in a state of shock, confusion, or self-blame. However, parents’ acceptance is extremely important for better quality of caring, to the healthy social and emotional child development, and to make the best decisions regarding gender assignment.Objective: To describe the acceptance process of parents that have children with sex chromosomes mosaicism DSD.Methods: This study used a mixed-method with a sequential explanatory approach, which was preceded by quantitative data collection followed by qualitative. The total respondents consisted of 14 mothers and 12 fathers of 14 sex chromosome mosaicism DSD patients with XX/XY, X/XY, XYY or XXY variants. Quantitative data were collected using the Indonesian version of the Parental Acceptance-Rejection Questionnaire (PARQ), and interviews were conducted to determine the acceptance process.Results: Most acceptance cases were based on the surgical stage completion in which a higher number of mothers (71.43%) than fathers (50%).Conclusion: It is uneasy for parents to accept children with sex chromosome mosaicisms DSD, hence the fathers struggle more than mothers in accepting those affected. To the best of our knowledge this is the first study in Indonesia to help parent understand and accept their child condition.